Surveillance of Shark Species Utilization at the Cilacap Ocean Fishing Port(Indonesia) using a Systems Approach - Priyanto, Nanang; NURANI, TRI WIJI; Solihin, Iin (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2026)
The utilization of shark species in Indonesia still encounters legal violations, thus necessitating an effective surveillance system. This study aims to identify the issues within the surveillance systemregarding the utilization of shark species at the Cilacap Ocean Fishing Port (PPS Cilacap). The studyuses a system approach, limited to the system analysis stage. The results showed that there are stillproblems in the shark species utilization monitoring system at PPS Cilacap. These problems resultin violations that continue to occur, especially concerning the legal regime of Regional FisheriesManagement Organizations (RFMOs). The problems identified in the conclusions of this study coverseveral aspects. Regarding regulations and institutions, the mandate holders lack synergy, lawenforcement remains weak, and support from management institutions for surveillance agencies isinsufficient. Regarding surveillance procedures and budget, the existing standard operatingprocedures (SOPs) do not represent surveillance needs in accordance with legal regulations onshark management, and the available budget is inadequate. Regarding facilities and infrastructure,surveillance facilities for shark species have not been utilized at PPS Cilacap, and unreported fishingstill occurs. Regarding human resources, the number of fisheries inspectors does not meet actualneeds, while vessel captains and owners' knowledge and legal awareness remain limited. Toaddress these issues, the recommended strategies include the maintenance and development ofport facilities at PPS Cilacap, the integration of information systems among institutions, thedissemination of shark governance, the recruitment, education, and training of fisheries inspectors,the revision of SOPs, and comprehensive law enforcement. Keywords: PPS Cilacap; shark; surveillance system